Quantification of ghrelin and des-acyl ghrelin in human plasma by using cubic-selected reaction-monitoring LCMS. (May 2014) - Sidibé, Jonathan; Varesio, Emmanuel; Hopfgartner, Gérard
Background: Ghrelin is a peptide hormone generally measured in plasma by immunoassays. LCMS/MS was investigated as an alternative method in particular for the quantification of the two forms of the peptide with improved selectivity.Materials & methods : A LCMS assay using a cubic-selected reaction-monitoring (LCSRM 3 /MS) mode was developed for the quantification of ghrelin and des-acyl ghrelin in human plasma.Results : The LCSRM 3 /MS method was found to be linear from 50–75 to 2500 pg/ml for the ghrelins using a 0.5-ml plasma sample. The accuracies and precisions at LOQ for des-acyl ghrelin (50 pg/ml) and ghrelin (75 pg/ml) were found to be better than 91 and 2%, respectively. Blood and plasma stabilization was found to be essential for good assay performance.Conclusion : Compared to the LCSRM/MS method the addition of an additional MS step did significantly improve the selectivity and therefore the sensitivity. The LCSRM 3 /MS method could be successfully applied for the quantification of ghrelin and des-acyl ghrelin in human plasma samples.